Unperceived Pregnancies: A Review - DÖNMEZ, MELİKE (KLINIK PSIKIYATRI DERGISI, 2017)
Unperceived pregnancy is defined as a pregnancy noticed after the 20th week of gestation, sometimes not until birth. Women may not notice the physiological manifestations of pregnancy, may not know the existence of the growing baby and not take on the role of motherhood, neither emotionally nor socially. Despite its tragic consequences, this condition observed in women of all ages, races, cultures and socioeconomic levels in the world is unfortunately not well known and the women concerned are suffer misunderstandings. They may be exposed to negative judgments, accusations and even legal sentences. Furthermore, even health workers may not fully understand unperceived pregnancies and not consider it in their differential diagnosis. In extreme cases, this may lead to maternal and infant deaths. It is crucial for health workers who encounter unperceived pregnancies to refer these patients for mental health support, and for mental health professionals to be fully aware of the condition and provide appropriate support. When it comes to legal considerations, it is vital to understand the situation of these women and provide the appropriate forensic approach. This multidimensional review approaches unperceived pregnancies in their medical, psychological, legal and ethical aspects. We aim to raise awareness regarding unperceived pregnancies and help future developments on this issue.
Keywords: Pregnancy; denial of pregnancy; unperceived pregnancy; dissociation; psychosis; DENIED PREGNANCY; NEONATICIDE; WOMEN